Power transformer magnetization under different frequency supply - Tan Tian Hoon (School of Electrical System Engineering, University Malaysia Perlis, 2011)
Transformer is a vital link in a power system which has made possible the power generated at low voltage to be stepped up to extra high voltages for transmission over long distances and then transformed to low voltages for distribution substation. This project specify about the different frequency supply to no load loss single phase transformer. Power loss is the energy dissipated during the cycling of a steel magnetic state at a frequency and peak induction relatable to its end application. This loss may be subdivided into two principle components, hysteresis loss and eddy-current loss in core laminations. Increasing of the thickness, power losses also increase. The hysteresis loss is directly proportional to frequency supply and to the area of hysteresis loop for the material used. Under operational condition, the hysteresis loss and eddy-current loss are practically constant for a given applied voltage and unaffected by the load on the transformer. Normally the power transformer is design for 50Hz or 60Hz operate. In this project, the transformer performance in term of magnetization that affected by various frequency will be evaluated